The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s13046-018-0949-2
|View full text |Cite|
|
Sign up to set email alerts
|

GPR119 agonist enhances gefitinib responsiveness through lactate-mediated inhibition of autophagy

Abstract: BackgroundLigand-dependent activation of the G-protein coupled receptor 119 (GPR119) lowers blood glucose via glucose-dependent insulin secretion and intestinal glucagon-like peptide-1 production. However, the function of GPR119 in cancer cells has not been studied.MethodsGPR119 expression was assessed by real-time qPCR and immunohistochemistry in human breast cancer cell lines and breast cancer tissues. Cell proliferation and cell cycle analyses were performed by Incucyte® live cell analysis system and flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…Lactate may be a potential and critical contributory factor in the regulation of immune function in sepsis. It has been reported that increased production of lactate suppressed autophagy in cancer cells (41). In the present study, it was revealed that lactate treatment decreased the autophagy marker LC3-II and increased p62 in the HK-2 cells stimulated with LPS.…”
Section: Discussionsupporting
confidence: 61%
“…Lactate may be a potential and critical contributory factor in the regulation of immune function in sepsis. It has been reported that increased production of lactate suppressed autophagy in cancer cells (41). In the present study, it was revealed that lactate treatment decreased the autophagy marker LC3-II and increased p62 in the HK-2 cells stimulated with LPS.…”
Section: Discussionsupporting
confidence: 61%
“…Thus, lactate sustains constitutively high levels of active Rheb and, in turn, constitutively active mTORC1. Although surprising, this is consistent with a recent report showing that autophagy, which is suppressed by mTORC1, can be inhibited by lactate [4]. Lactate administration has also been shown to activate mTORC1 in muscle of adult mice [5].…”
supporting
confidence: 92%
“…However, GPR119 is only activated by eCBs analogues, including oleoylethanolamide and palmitoylethanolamide, rather than pCBs or sCBs. Therefore, GPR119 is not discussed in detail here, other than to outline that its agonism by specific ligands (such as MBX-2982 or GSK1292263), re-sensitises breast cancer cells that have developed resistance to gefitinib [74]. Uniquely, CBD is a ligand for the orphan GPCRs, GPR3, GPR6 and GPR12 (discussed in Section 3.2.3).…”
Section: Non-thc Cannabinoids Are Ligands For Calcium Selective Ion Channels and Orphaned/de-orphaned G-protein-coupled Receptorsmentioning
confidence: 99%